LA ÉTICA Y SU INFLUENCIA EN LA GESTIÓN INSTITUCIONAL DE ENTIDADES EDUCATIVAS PRIVADAS DE ENSEÑANZA SUPERIOR - Begazo Villanueva, José Domingo (2012)
Educational institutions have significant social and cultural functions in the construction of society and with respect to the major changes taking place in the world, especially when looking for different ways to reduce the inequitable distribution of wealth, promote social mobility and study and formulate options for solving priority problems. The values and ethical behavior are part of these issues. The professions and professionals from all areas of knowledge, occupy a significant place in the social world, as they provide goods and services required by society itself. Its performance and performance are always on the look of the sectors, groups and individuals (local, regional, national and international). Ethical behavior is an intrinsic part of the profession and the meaning of life and projects of subjects. It is also, along with the professional and technical competence, so that people can better appreciate your work. Today there is a special sensitivity to ethical and social demands regarding professionals. It most often insists on the importance of incorporating ethical elements in their training and in the field of scientific research and socio - cultural. Have been introduced gradually subjects of ethics and professional conduct (9) in university degrees and higher education institutions and the countries of Western Europe and the United States of America and Canada have increased ethics committees, primarily in the fields of science. Have appeared recently in very diverse sectors, such as: universities, ministries and agencies, national and international. Professional ethics is an interdisciplinary field, which can help reduce the isolation that are the specialties, to integrate them into an overall perspective. The ethical responsibility of all professions, not just to each of them, but also to the fields of interaction that occur to solve complex social problems.